2021
DOI: 10.1155/2021/6684906
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Behavior Analysis and Robust Synchronization of a Novel Fractional-Order Chaotic System with Multiwing Attractors

Abstract: To enrich the types of multiwing chaotic attractors in fractional-order chaotic systems (FOCSs), a new type of 3-dimensional FOCSs is designed in this study. The most important contribution of this FOCS consists in the coexistence of multiple multiwing chaotic attractors, including 2-wing, 3-wing, and 4-wing attractors. It is also indicated that the minimum order that the system can exhibit chaotic behavior is 0.84. Then, based on certain fractional stability criteria, a robust synchronization controller is de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…[8] constructed two Hamiltonian conservative chaotic systems and designed a pseudorandom signal generator based on these systems using an FPGA, passing the NIST tests. Moreover, various chaotic systems have exhibited distinct dynamic behaviors such as hyper-chaos [9], multi-stability [10], offset-boosted behavior [11], multi-wing attractors [12], and multiscroll attractors [13]. These traits underline the inherent advantages of chaotic systems in the domain of encryption [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…[8] constructed two Hamiltonian conservative chaotic systems and designed a pseudorandom signal generator based on these systems using an FPGA, passing the NIST tests. Moreover, various chaotic systems have exhibited distinct dynamic behaviors such as hyper-chaos [9], multi-stability [10], offset-boosted behavior [11], multi-wing attractors [12], and multiscroll attractors [13]. These traits underline the inherent advantages of chaotic systems in the domain of encryption [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Finally, it is found that the anti-phase synchronization between two pendulums is achieved by the tiny vibrations propagated by the beam, that is, by beam coupling [ 65 ]. In recent years, there are more and more research projects on how to apply the synchronization phenomenon to various fields, such as nonlinear systems [ 66 , 67 , 68 ] and complex network synchronization behavior [ 69 , 70 , 71 , 72 ].…”
Section: Introductionmentioning
confidence: 99%